Development of an error‐detection examination for conservative dentistry education - Masahiro Yoneda; Kazuhiko Yamada; Toshio Izumi; Etsuko Matsuzaki; Michito Maruta; Junko Hatakeyama; Hiromitsu Morita; Takashi Tsuzuki; Hisashi Anan; Takao Hirofuji (Wiley, 2020)
Abstract Objective For dental students, textbooks and lectures provide basic knowledge, and simulated and actual clinical training provide learning in technical and communication skills. At our college, conservative dentistry is taught in the third and fourth years of a 6‐year undergraduate degree. Clinical training is undertaken subsequently in the fifth year and includes cavity preparation and composite resin filling tasks. However, despite the clinical importance of a full understanding surrounding these procedures, sixth‐year students occasionally provide incorrect answers regarding these procedures in assessments. Although they demonstrated a basic understanding of the procedures, they may have forgotten the acquired knowledge during their clinical training. Therefore, we developed an error‐detection examination to evaluate and improve fifth‐year students' knowledge. Methods Written detailed treatment procedures for standardized, typical, cases were presented to students. Some critical steps were intentionally written incorrectly, and students had to identify and correct these. After correcting the steps, students gave a presentation to their peers on their corrections. This was followed by a summary of the correct answers and a short lecture by the teacher. Students then completed a questionnaire investigating their experience of the examination. Results Students misunderstood some key treatment steps, such as pretreatment of composite resin filling, amalgam removal, and ceramic inlay fitting. The questionnaire revealed that this method of testing applied knowledge was new to students and helped them to identify knowledge gaps. The test also increased their motivation to study conservative dentistry. Students were open to taking similar tests in different areas. Conclusion Although conservative dentistry is a basic field of dental treatment, mistakes in treatment can lead to early treatment failure or reduce the lifetime of a restored tooth. Therefore, students need to have a deep understanding of procedures. Error‐detection examinations may help students identify knowledge gaps and provide useful feedback to teachers to identify areas that they should stress in earlier years.